Behavioral Measurements of a Temporally Precise Motor Code for Birdsong - Glaze, Christopher M. (J Neurosci, 2007)
There are conflicting data on the timescale for the representation of adult zebra finch song. Acoustic structure and perturbation studies suggest that song is divided into discrete vocal elements, or syllables, lasting 50–200 ms. However, recordings in premotor telencephalic nucleus HVC (used as proper name) and RA (robust nucleus of arcopallium) suggest that song is represented by sparse, fine-grained bursting on the 5–10 ms timescale. We previously found patterns of timing variability that distinguish individual syllables and repeat across multiple 500- to 1000-ms-long motifs (Glaze and Troyer, 2006). Here, we extend our methods to analyze whether this is attributable to a syllable-based code or representations on a finer timescale. We find evidence for the latter. First, identity-dependent timing is dominated by independent variability in notes, finer song segments that compose a syllable; for example, the length of a note is no more correlated with other notes in the same syllable than it is with notes in other syllables. For a subset of notes, clear modulation in spectral structure allowed for accurate timing measurements on the 5–10 ms timescale. Temporal independence holds at this scale as well: the length of an individual 5–10 ms song slice is correlated with the same slice repeated 500–1000 ms later, yet is independent of neighboring slices. We propose that such fine-grained, persistent changes in song tempo result from an interaction between slow modulatory factors and precisely timed, sparse bursting in HVC and RA.